2017
DOI: 10.15406/jdhodt.2017.07.00240
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Study of Oral Human Papillomavirus (Hpv) Infection among Gathered Shish Smokers

Abstract: Background: Oral cancer is one of the 10 top existing cancers and high risk human papillomavirus (HR-HPV), represent one of its main causes. Therefore, the aim of the present study was to determine the role of mixed shisha smoking (in groups) in transmission of HPV, as well as, to assess the cellular proliferative activity that might be caused by shisha smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(20 reference statements)
1
0
0
Order By: Relevance
“…1.85-28.16) and 5.17 The prevalence of oral HR-HPV infection observed in this study (11%) was consistent with some studies, [14][15][16][17] whereas in contrast with the large-scale studies from the United States carried out in >5000 participants, which reported an overall prevalence of OHPV infection of 6.9%, 18 China (0.67%), Costa Rica (1.3%), United Kingdom (2.2%), Italy (4%), and Brazil (3.9%), respectively. 6,[19][20][21][22] The prevalence observed in this study was lower than that observed in the study previously conducted in Pakistan, which was 24.5% T A B L E 1 Information and association of HR-OHPV with sociodemographic, addictive habits, and oral hygiene status among participants attending the dental department 23 whereas, higher in comparison to the study conducted by Irshad et al 24 reported a prevalence of 7.6% in school-going children in Karachi,…”
Section: Resultssupporting
confidence: 92%
“…1.85-28.16) and 5.17 The prevalence of oral HR-HPV infection observed in this study (11%) was consistent with some studies, [14][15][16][17] whereas in contrast with the large-scale studies from the United States carried out in >5000 participants, which reported an overall prevalence of OHPV infection of 6.9%, 18 China (0.67%), Costa Rica (1.3%), United Kingdom (2.2%), Italy (4%), and Brazil (3.9%), respectively. 6,[19][20][21][22] The prevalence observed in this study was lower than that observed in the study previously conducted in Pakistan, which was 24.5% T A B L E 1 Information and association of HR-OHPV with sociodemographic, addictive habits, and oral hygiene status among participants attending the dental department 23 whereas, higher in comparison to the study conducted by Irshad et al 24 reported a prevalence of 7.6% in school-going children in Karachi,…”
Section: Resultssupporting
confidence: 92%